Green Synthesis of 6-[2-Aminothiazol-4-yl]-2-furylchromone - Prabha Sharma, Vinay; Kumar, Rakesh (Asian Journal of Chemistry, 2014)
Synthesis of 2-aminothiazoles through Hantzsch method involves the use of bromine. An 2-aminothiazole system 6-[2-aminothiazol-4-yl]-2-furylchromone has been synthesized green chemically from 6-chloroacetyl-2-furylchromone and 6-acetyl-2-furylchromone during present study. The structures of new compounds were elucidated on the basis of IR and PMR-spectra.